The Relationship between Yemeni EFL Postgraduate Students’ Perceptual Learning Styles and Language Learning Strategies - Al-Hubaishi, Belal Abdullah Mohammed; Al-Mekhlafi, Mohammad Abduh Ahmad (International Journal of Language and Literary Studies, 2023)
Learning styles and strategies are among the most influential factors that account for some differences in how students learn. Because traditional teaching methods are still employed at universities, Yemeni instructors need to be aware of students’ learning styles and strategies for improving classroom teaching and learning. This study intended to investigate the relationship between Yemeni EFL postgraduate students’ Perceptual Learning Style Preferences (PLSP) and their Language Learning Strategies (LLSs). A total of 45 Yemeni postgraduate students (males = 14 and females = 31) enrolling in master’s degree studies at Sana’a University completed two kinds of questionnaires adapted from Reid’s (1987) Perceptual Learning Style Preference Questionnaire (PLSPQ) and Oxford’s (1990b) Strategy Inventory of Language Learning (SILL). The findings showed that kinesthetic, auditory, and tactile were the major learning style preferences (LSPs), whereas group and individual were the least preferred minor LSPs among the participants. Metacognitive, compensation, and cognitive strategies were the most frequently used, while memory and affective strategies were the least frequently used. A statistically significant relationship was found between the participants’ PLSP and their LLSs. These findings may help curriculum developers and language instructors incorporate learning styles and strategies into the syllabus to accommodate individual differences and facilitate learning.